Exploring Work-Related Experiences of Newly Hired Hospital Nurses in Ghana: A Qualitative Study - Ernest Darkwah PhD; Francis Annor PhD; Seth Oppong PhD; Sylvia Hagan MPhil (SAGE Publishing, 2024)
Introduction Early work-related experiences of newly hired employees can have important implications for their work performance over time and their future health and well-being trajectories. In health care work, such outcomes may hold implications for the services delivered and the patients whose lives depend on them. Objective(s) This study was conducted to explore the work-related experiences of newly hired hospital nurses in Ghana. Methods Using qualitative methods, thirty-six (36) newly hired nurses in three (3) hospitals in the Eastern Region of Ghana were purposively sampled and interviewed. Thematic network analyses were applied to the data collected. Results Five main themes emerged which summarized the experiences of the nurses. The themes indicated that newly hired nurses experienced the nursing profession as stressful and yet fulfilling, different from their preentry expectations with multiple sources of stressors and resources. Religion and faith, family support, and a perceived lack of suitable alternative sources of income emerged as the main motivators of the intention to stay. Conclusion The findings suggest a highly stressful and quite unpredictable work environment for newly hired nurses. Despite this, they are determined to stay on the job. Employee assistance programs that have specialized components targeted at providing emotional and psychosocial assistance to newly hired nurses are recommended.